rTMS-induced neuroimaging changes measured with structural and functional MRI in autism - Kang, Xiaodong; Chen, Kai; Wang, Fei; Mu, Linyi; Lei, Zengzhen; Zhang, Rufei; Wang, Zedong; Zhang, Tao (Frontiers in Neuroscience, 2025)
IntroductionAutism Spectrum Disorder (ASD) is a complex neurodevelopmental condition characterized by deficits in social communication, repetitive behaviors, and restricted interests. Despite increasing prevalence, effective therapeutic interventions remain limited. Repetitive transcranial magnetic stimulation (rTMS) has emerged as a promising non-invasive neuromodulation technique; however, its neural mechanisms and clinical efficacy in children with ASD require further investigation.MethodsThis study enrolled 14 children diagnosed with ASD to undergo a structured rTMS intervention. Neuroimaging data—including voxel-based morphometry (VBM) and resting-state functional connectivity (FC)—as well as behavioral assessments were collected before and after the intervention to evaluate changes in brain structure, function, and symptomatology.ResultsPost-intervention analyses revealed significant increases in gray matter volume (GMV) in the cerebellar Vermis, Caudate nucleus, and Postcentral gyrus. Additionally, enhanced functional connectivity was observed between the Fusiform gyrus, Temporal cortex, Frontal cortex, and Precuneus. Correlation analyses indicated that these neuroimaging changes were significantly associated with improvements in behavioral scores.DiscussionThese findings suggest that rTMS may exert therapeutic effects in children with ASD by modulating cerebellar development and cognitive control networks. The observed structural and functional brain changes support the potential utility of rTMS as a neuromodulatory intervention for ASD. Further studies with larger cohorts are needed to confirm these preliminary results and elucidate the mechanisms underlying rTMS-induced symptom improvement.